Cost Model for end-milling of AISI D2 tool steel - Mohamed, Elhadie; A.N., Mustafizul Karim; Amin, A. K. M. Nurul (2011)
In this research paper, user-friendly and accurate mathematical model for estimating the cost of end-milling of AISI D2 tool steel using Polycrystalline Cubic Boron Nitride (PCBN) cutting tool inserts is developed. Initially, the different components of machining cost were identified, followed by establishment of equations to determine their values. Then, the required experimental and non-experimental data were collected and the bottom-up approach was adopted for evaluating the cost of machining corresponding to each of fifteen experimental runs. The Response Surface Methodology (RSM) was used to develop the model in which the cost of machining is given as a function of the machining parameters; cutting speed, feed per tooth, and depth of cut, and expressed in Ringgit Malaysia per cubic cm (RM per cm)3. Analysis of Variance (ANOVA) was utilized to check the adequacy of the developed model. The developed model was found to be statistically adequate.